Hubungan Kualitas Tidur Dengan Konsentrasi Belajar Pada Siswa/I SMP 1-6 Kartika Padang - firda damba wahyuni; Chichi Hafifa Transyah (Jurnal Amanah Kesehatan, 2023)
Based on data from the Ministry of Health, 5.2% of school-age children experience a decrease in their concentration and interest in learning, a decrease in their interest in learning and is expected to double every 5 years to reach more than 45%. Report of the Ministry of Education and Culture of Padang City for the 2022/2023 school year Kartika Middle School 1-6 is one of the private junior high schools in the city of Padang ranked 30 out of other private junior high schools in the city of Padang.Objective this researchto determine the relationship between sleep quality and student concentration at SMP 1-6 Kartika Padang in2023. Research and data collection were conducted at Kartika 1-6 Middle School from February to June 2023 with a sample of 66 respondents, the sampling technique usedTotal Sampling. The data obtained were analyzed univariately with a frequency distribution and bivariately with statistical testsWho Square. The results of the univariate variable showed poor learning concentration (55%) and poor sleep quality (62%). Based on the results of statistical tests, there is a significant relationship between sleep quality and learning concentration p=0.02(p<0.05). It can be concluded that there is a relationship between sleep quality and student learning concentration at SMP 1-6 Kartika Padang. It is suggested that this research is used as basic data for the development of school policies on student learning concentration that is affected by poor sleep quality. Keyword : Study concentration; sleep quality